Human capital returns to cash transfers in Uganda: does it matter in the long run?. Issue 1 (2nd January 2020) - Dietrich, Stephan; Malerba, Daniele; Barrientos, Armando; Gassmann, Franziska; Mohnen, Pierre; Tirivayi, Nyasha
ABSTRACT: The paper reports on an ex-ante evaluation of the nationwide scale up of two pilot cash transfer programmes in Uganda. We use panel data to estimate consumption elasticities of child health status and school enrolment. They provide the main parameters of a micro-simulation model predicting cash transfer effects on human capital accumulation and feedback effects on consumption. Quantifying year on year costs and direct and indirect benefits, we track the annual trend in rates of return. The findings indicate important gains in child health, schooling, and income growth associated with programme participation. The rates of return improve over the medium term but remain negative after 10 years. These findings underline the need to regard cash transfers as longer-term social investment instead of short-term costs.